Stylistyka i estetyka w przekładzie - wyzwania translatorskie (na podstawie opowiadania "Nema povratka" Miodraga Bulatovicia) = Stylistics and aesthetics of translation - challenges for the translator (based on the story "Nema povratka" written by Miodrag Bulatović) - Fudala, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this paper is to answer the question how the autor`s style influences the work of the translator. The analyzed examples come from the story "Nema povratka" written by Miodrag Bulatović. The final part of the article summarises the process of translation and indicates various difficulties that have arisen during this process. The most important conclusion is that autor`r aesthetics is present in the form of translation.
Keywords: wyzwania translatorskie; stylistyka przekładu; estetyka przekładu; funkcjonalność przekładu; challenges for the translator; stylistics of translation; aesthetics of translation; functionality of translation